The relationship between family support and treatment adherence in patients with tuberculosis in Deli Serdang Regency, Indonesia, 2022: A cross-sectional study - Rahmad Gurusinga; Afrizal Afrizal; Adang Bachtiar; Firdawati Firdawati; Rizanda Machmud; Erlina Burhan; Jendrius Jendrius; Rima Semiarty (Kashan University of Medical Sciences, 2024)
Background: Tuberculosis (TB) remains a significant global health challenge, with an ongoing increase in the number of TB cases and deaths each year. This rise is largely attributed to high dropout rates from treatment due to non-adherence. Family support plays a crucial role in enhancing TB treatment adherence.Objectives: This study aimed to analyze the relationship between emotional, appreciation, informational, and instrumental support from family members and the level of treatment adherence among TB patients in Deli Serdang Regency, North Sumatera Province, Indonesia, in 2022.Methods: A cross-sectional study was conducted involving 150 TB patients who were randomly selected from Deli Serdang Regency, Indonesia, in 2022. Data were collected using a valid Likert scale questionnaire to evaluate the emotional, appreciation, informational, and instrumental support received from family members, as well as treatment adherence among TB patients. Descriptive statistics, chi-square tests, and multivariate logistic regression analyses were performed using SPSS version 21.Results: Among the respondents, 62% were male, 55.3% had a high level of education, and 70% were over 35 years old. The analysis revealed that only instrumental support did not show a significant effect (P=0.072), whereas emotional (P=0.001), appreciation (P=0.001), and informational (P=0.002) support had significant impacts on treatment adherence. The multivariate analysis indicated that only emotional support (P=0.044, OR=3.2, 95% CI: 1.0-9.8) and appreciation support (P=0.021, OR=4.5, 95% CI: 1.3-15.9) significantly influenced TB patients' adherence to their treatment.Conclusion: While appreciation support has a greater influence than emotional support on treatment adherence in TB patients, it is essential for healthcare providers and families to offer all types of support to enhance treatment adherence among these patients.